2019
DOI: 10.1002/dneu.22685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Song Experience and Song Quality on Immediate Early Gene Expression in Female Canaries (Serinus canaria)

Abstract: Female songbirds are thought to make mate choices based on aspects of male song quality. Male canaries (Serinus canaria) produce songs with "special" syllables that have been shown to be highly salient to female listeners -eliciting high rates of sexual displays and enhanced immediate early gene (IEG) expression. Immunohistochemistry for the IEG ZENK was used to examine the effects of experience with these syllables on activity in the caudal mesopallium (CMM) and nidocaudal mesopallium (NCM), two auditory area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Neural activities in higher auditory regions of females also indicated that evidence of encoding for sound differences or sensitivity depended on social context or type of sounds (Diez, Cui, & MacDougall‐Shackleton, ; Van Ruijssevelt et al, ; Woolley & Doupe, ; Yoder, Phan, Lu, & Vicario, ). Moreover, song experience dependent neural activities also observed in CMM and NCM in other species female songbird (Haakenson, Madison, & Ball, ; Kato, Kato, Hasegawa, & Okanoya, ). While various studies have reported about contribution of CMM and NCM for female sound recognition, it is little known about fundamental regional differences or neural encoding for acoustic factors.…”
Section: Introductionmentioning
confidence: 68%
“…Neural activities in higher auditory regions of females also indicated that evidence of encoding for sound differences or sensitivity depended on social context or type of sounds (Diez, Cui, & MacDougall‐Shackleton, ; Van Ruijssevelt et al, ; Woolley & Doupe, ; Yoder, Phan, Lu, & Vicario, ). Moreover, song experience dependent neural activities also observed in CMM and NCM in other species female songbird (Haakenson, Madison, & Ball, ; Kato, Kato, Hasegawa, & Okanoya, ). While various studies have reported about contribution of CMM and NCM for female sound recognition, it is little known about fundamental regional differences or neural encoding for acoustic factors.…”
Section: Introductionmentioning
confidence: 68%
“…The intermediate medial HV was suggested to participate in the memory formation for avoidance learning in chicks (Patterson et al 1990) and recognition following visual imprinting (Horn 1990). Additional past studies in the caudal medial mesopallium (CMM) and nidocaudal mesopallium (NCM), two important auditory areas, previously associated these brain areas to perceptual processing of song and the formation of auditory memories (Lynch et al 2013;Haakenson et al 2019). Respectively, this information could align with social and object recognition (visual-based) impairments and audit o r y p a t h w a y a b n o r m a l i t i e s f o l l o w i n g A d n p haploinsufficiency (Vulih-Shultzman et al 2007;Malishkevich et al 2015;Amram et al 2016;Hacohen-Kleiman et al 2018, as well as intellectual disability, autism-like traits, and atypical auditory brain stem response (ABR) in the ADNP syndrome patients (Helsmoortel et al 2014;Hacohen-Kleiman et al 2019;Van Dijck et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Female canaries exhibit copulation solicitation displays with higher frequency when exposed to playbacks of male songs containing 'sexy' syllables (Vallet et al, 1998;Vallet and Kreutzer, 1995). Additionally, the expression of immediate early genes ZENK and c-Fos in two auditory forebrain regions, the caudal mesopallium and nidocaudal mesopallium (areas analogous to secondary auditory cortices in mammals), is higher in female canaries exposed to male songs including 'sexy' trills than to songs without these sexy trills (Leitner et al, 2005;Monbureau et al, 2015), although these responses may depend on the acoustic context (Haakenson et al, 2019).…”
Section: Sex Differences In Trill Productionmentioning
confidence: 98%